Pengaruh Komposisi Katalis H-Zeolit Dan Suhu Reaksi Pada Proses Pembuatan Fatty Acid Alkyl Ester Dari Minyak Limbah Ikan Patin Dan Isooktanol - Randi Farlindo; Nirwana Nirwana; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Fatty acid alkyl esters found in nature in the form of esters of glycerol with fatty acids or hydroxyl groups are also formed with the phosphate ester such as phospholipids, the usual method used to form fatty acid alkyl ester is by esterification, interesterification, alcoholysis and asidolisis. Transeterifikasi reaction is a reaction between oils (triglycerides) to produce alcohol Fatty acid alkyl esters. One commercial product is the plasticizer. Plasticizers from bio-oil production is still very limited, it is necessary to develop a bio-oil-based plasticizers. In this research, the synthesis of plasticizers by transesterification reaction using an activated natural zeolite catalysts to H-zeolite, with variations in temperature (140 oC, 160 oC and 180 oC) and the composition of the H-zeolite (10%, 15%, and 20%) weight-based waste oil catfish, with a fixed variable is the molar ratio of 1:6, the reaction time of 6 hours and stirring speed 200 rpm .. Transesterification of the test results showed that the temperature and composition of the H- zeolite catalysts affect reaction rates for the reaction to reach equilibrium. The best operating conditions obtained in this study is 160 oC temperature, catalyst composition 15%, stirring speed 200 rpm and reaction time 6 hours reaction resulting in a conversion of 23.4%. Characteristics of plasticizers produced in this study meets the standards of commercial plasticizers viscosity 8.33 mPa s, Specific Gravity (30 oC) 0.85 and saponification number is 137.308 mgKOH / grSampel.